Diagnostic Significance of Clinicopathological Concordance in Various Spectrums of Skin Disorders - Kafle, Santosh Upadhyaya; Chaudhary, Dilip; Sabrina Yamu, Sabrina Yamu; Jha, Krishna (Birat Journal of Health Sciences, 2020)
Introduction: Wide spectrums of skin disorders exist in the world. Skin biopsy is a proven method for allying the dermatologist in overcoming the diagnostic dilemmas that occur in consultations. The different level of clinicopathological concordance, either full or partial and discordant study may reflect the agreement between the clinicians and pathologists for diagnosing spectrum of skin disorders. Objectives: To analyze the histopathological spectrum of skin diseases emphasizing on the diagnostic significance of its clinicopathological concordance. Methodology: This is a prospective cross sectional hospital based study of skin biopsies obtained in the Department of Pathology, at Birat Medical College and Teaching Hospital from Dec 2016 to Jan 2020. Demographic data, nature of lesions, correlation between clinicopathological concordance and histopathological diagnosis were analyzed using SPSS version 16. Result: Among 111 skin biopsies, female gender of 19-39 years age groups was predominant. The commonest histopathological diagnosis of skin biopsies was under infectious and bacterial origin category (24.3%) reflecting non-neoplastic nature mostly. The overall clinicopathological concordant was 78.38% (fully concordant 27.93% and partially concordant 50.45%) and discordant 21.62%. Nature of lesions was strongly correlated (p<0.05) with age group, while it was weak with gender. However, the relationship was very strong between histopathological diagnosis and clinicopathological concordance (p<0.05%). Conclusion: Findings suggest that the clinicopathological concordance correlated well in histopathologically diagnosed disease category of skin disorders. This reflects the high diagnostic value of histopathological examinations for diagnosing different spectrum of skin disorders.